Globalização e a isomorfia curricular na base nacional comum curricular: é possível resistir às mudanças? - Silva, Phelipe Martins da (2024)
This article deals with the current Brazilian educational policy aimed at basic education. With the advent of the high school reform, instituted by Federal Law No. 13.415/2017, the federative units needed to adapt to the National Common Curriculum Base (BNCC), a normative document that contains the guidelines for the implementation of local curricula. However, this political movement of restructuring the curriculum takes place in a scenario where global trends are taken as a reference in the construction of national and regional policies. In this sense, the process called isomorphy or curricular imitation ends up framing and restricting the development of educational policies that should meet the specificities of a country like Brazil, diverse, multicultural, with continental dimensions and full of inequalities and social asymmetries that tend to worsen with the imposition of the BNCC. Thus, the resistance to this internationalized policy, marked by globalization, aligned with the assumptions of neoliberalism, shows itself as a creative alternative to the nefarious demands of the market.